2013
DOI: 10.2139/ssrn.2339273
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Tempered Stable Distribution

Abstract: In this paper we introduce a new parametric distribution, the Mixed Tempered Stable. It has the same structure of the Normal Variance Mean Mixtures but the normality assumption leaves place to a semi-heavy tailed distribution. We show that, by choosing appropriately the parameters of the distribution and under the concrete specification of the mixing random variable, it is possible to obtain some well-known distributions as special cases.We employ the Mixed Tempered Stable distribution which has many attractiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…As shown in Rroji and Mercuri (), if V ∼Γ( a , b ), we get some well‐known distributions used for modeling financial returns as special cases. For instance, if α =2, the Variance Gamma introduced in Madan and Seneta () is obtained.…”
Section: Univariate Mixed Tempered Stablementioning
confidence: 94%
See 2 more Smart Citations
“…As shown in Rroji and Mercuri (), if V ∼Γ( a , b ), we get some well‐known distributions used for modeling financial returns as special cases. For instance, if α =2, the Variance Gamma introduced in Madan and Seneta () is obtained.…”
Section: Univariate Mixed Tempered Stablementioning
confidence: 94%
“…Suppose F is an infinitely divisible distribution on double-struckR+ with cumulant function Φ V . Then, there is a convolution semigroup of probability measures ( F t ) t ⩾0 on double-struckR+ and a Lévy process ( V t ) t ⩾0 such that V t ∼ F t for t ⩾0 and normalΦVt(u)=tnormalΦV(u).In Rroji and Mercuri (), it is shown that the MixedTS()μt,β,α,λ+,λFt distribution is infinitely divisible. According to the general theory, see, for example, proposition 3.1, p. 69 in Cont and Tankov (), there exists a Lévy process ( Y t ) t ⩾0 such that Y11emMixedTS()μ,β,α,λ+,λF1.…”
Section: Univariate Mixed Tempered Stablementioning
confidence: 99%
See 1 more Smart Citation
“…By modifying the Lévy measure of a stable law, we can introduce the tempered stable family from both univariate and multivariate perspectives (Boyarchenko and Levendorskiȋ (2000) and Boyarchenko and Levendorskiȋ (2002)). Formal and elegant definitions of tempered stable distributions and processes were proposed in the seminal study by Rosiński (2007) who employed a completely monotone function to transform the Lévy measure of a stable distribution (various parametric classes were discussed by Terdik and Woyczynski (2006), Bianchi et al (2010), Bianchi (2015), Rroji and Mercuri (2015), Grabchak (2016)). Two classes of distributions that are broader than the tempered stable class have been proposed, where Rosinski and Singlair (2010) introduced the generalised tempered stable class and Grabchak (2012) proposed the p-tempered stable class.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The main object of this paper is to present an option pricing model under the assumption that log returns are generated from a Lévy Mixed Tempered Stable (MixedTS hereafter) process. This process is built using the infinitely divisible property of the MixedTS distribution recently introduced by Rroji and Mercuri (2015) as a generalization of the Normal Variance Mean Mixture (NVMM hereafter) family of distributions. The relevance of Lévy processes has been widely investigated in financial modeling especially for asset prices (Carr and Wu, 2004a;Eberlein and Madan, 2009;Carr and Madan, 1999, see for instance) mainly due to the fact that these processes are able to handle with the stylized facts.…”
Section: Introductionmentioning
confidence: 99%